The impacts of viral marketing in influencing the consumer’s purchase decisions - Shahar, Nurul Shafinas; Wok, Saodah (2018)
The rapid growth of social networks is in fact being influenced by the usage of the Internet. Viral Marketing not only boosts the sales and business of online marketers but also affects the Corporate Reputation of the organization and the company concerned. Good response to the viral messages from consumers is important to influence and to persuade them when it comes to decision-making. Social networks such as Facebook, Instagram, WhatsApp and Twitter are the platforms used to circulate the digital contents especially in the social network sites (SNS). The rapid growth of the social networks’ acceptance together with the high number of users in Malaysia indirectly gives an advantage to the online business industry. Furthermore, the onslaught of technology and social media networks in communication provides marketers with a new platform in advertising their products and services. Therefore, this research is conducted to study the impacts of the viral in digital marketing in influencing consumers’ purchase-decision among Malaysians. This study is to determine the viral phenomena that will give significant impacts to consumers when deciding to buy certain products or services. The quantitative research design using the survey method is conducted and 266 respondents participated in the study. The results show that the more the messages are shared, the higher is the reputation of the organization concerned and this indirectly increases their sales. Moreover, with the Internet ease-of-use and high-speed data, most consumers are trying to gather the information about the products and services rendered through the Internet; and Viral Messages from Marketers somehow helps consumers in making purchase decisions.